Current status and future perspectives of platelet-derived extracellular vesicles in cancer diagnosis and treatment - Tongtao Zhuang; Shenrong Wang; Xiaoqian Yu; Xiaoyun He; Hongbin Guo; Chunlin Ou (BMC, 2024)
Abstract Platelets are a significant component of the cell population in the tumour microenvironment (TME). Platelets influence other immune cells and perform cross-talk with tumour cells, playing an important role in tumour development. Extracellular vesicles (EVs) are small membrane vesicles released from the cells into the TME. They can transfer biological information, including proteins, nucleic acids, and metabolites, from secretory cells to target receptor cells. This process affects the progression of various human diseases, particularly cancer. In recent years, several studies have demonstrated that platelet-derived extracellular vesicles (PEVs) can help regulate the malignant biological behaviours of tumours, including malignant proliferation, resistance to cell death, invasion and metastasis, metabolic reprogramming, immunity, and angiogenesis. Consequently, PEVs have been identified as key regulators of tumour progression. Therefore, targeting PEVs is a potential strategy for tumour treatment. Furthermore, the extensive use of nanomaterials in medical research has indicated that engineered PEVs are ideal delivery systems for therapeutic drugs. Recent studies have demonstrated that PEV engineering technologies play a pivotal role in the treatment of tumours by combining photothermal therapy, immunotherapy, and chemotherapy. In addition, aberrant changes in PEVs are closely associated with the clinicopathological features of patients with tumours, which may serve as liquid biopsy markers for early diagnosis, monitoring disease progression, and the prognostic assessment of patients with tumours. A comprehensive investigation into the role and potential mechanisms of PEVs in tumourigenesis may provide novel diagnostic biomarkers and potential therapeutic strategies for treating human tumours.